2008
DOI: 10.1128/jvi.02455-07
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I-Driven Evolution of Human Immunodeficiency Virus Type 1 Subtype C Proteome: Immune Escape and Viral Load

Abstract: Human immunodeficiency virus type 1 (HIV-1) mutations that confer escape from cytotoxic T-lymphocyte (CTL)recognition can sometimes result in lower viral fitness. These mutations can then revert upon transmission to a new host in the absence of CTL-mediated immune selection pressure restricted by the HLA alleles of the prior host. To identify these potentially critical recognition points on the virus, we assessed HLA-driven viral evolution using three phylogenetic correction methods across full HIV-1 subtype C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
161
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(175 citation statements)
references
References 67 publications
11
161
1
2
Order By: Relevance
“…Consistent with previous studies of HLA-APs in HIV clade B (2,16,18), HLA-APs were more frequently detected in Nef than in Gag and Pol. Also consistent with previous observations in Caucasian, African, Chinese, and Mexican populations (1,6,11,15,18), the number of HLA-B-associated polymorphisms in our cohort was higher than that of HLA-A-or HLA-C-associated polymorphisms, further supporting a dominant role of HLA-B in HIV evolution (32). An interesting feature of the Japanese population is that approximately 70% of individuals carry HLA-A*24:02 (23).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies of HLA-APs in HIV clade B (2,16,18), HLA-APs were more frequently detected in Nef than in Gag and Pol. Also consistent with previous observations in Caucasian, African, Chinese, and Mexican populations (1,6,11,15,18), the number of HLA-B-associated polymorphisms in our cohort was higher than that of HLA-A-or HLA-C-associated polymorphisms, further supporting a dominant role of HLA-B in HIV evolution (32). An interesting feature of the Japanese population is that approximately 70% of individuals carry HLA-A*24:02 (23).…”
Section: Discussionsupporting
confidence: 92%
“…HLA-APs were more frequently detected in Nef (occurring at 45 of 206 codons [21.8%]) compared to Gag (51 of 500 codons [10.2%]) or Pol (51 of 947 codons [5.1%]). Although HLA class I allele frequencies in Japan are somewhat distinct globally, the distribution of HLA-APs across HIV-1 proteins was consistent with that reported in previous studies of other populations infected with clade B or C (1,2,6,7,16). Broken down by HLA locus, the numbers of HLA-A-, HLA-B-, and HLA-C-associated polymorphisms were 78, 140, and 66, respectively, numbers that were also consistent with previous reports from Caucasian and African cohorts that HLA-B alleles restrict more associations than HLA-A or HLA-C alleles (1,6,18).…”
Section: Identification Of Hla-associated Polymorphisms In Chronicallsupporting
confidence: 89%
See 2 more Smart Citations
“…11 Human leukocyte antigen (HLA) class I-mediated CTL responses are important predictors of disease progression 12 that drive virus escape mutations that are highly adapted to the host environment. 4,[13][14][15][16][17][18] Recent studies employing ultradeep sequencing 3,19 confirmed dramatic shifts in the frequencies of epitope variants during the first weeks of HIV infection.…”
Section: Introductionmentioning
confidence: 99%